PENERAPAN METODE GUIDED NOTE TAKINGDISERTAIMEDIA MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPA TERPADU SISWA KELAS VIII SMP NEGERI 28 MERANGIN TAHUN PELAJARAN 2019/2020 - Ela Wiana; Leni Marlina; Rozana Zuhri (BIOCOLONY, 2021)
Based on the results of observations carried out in SMP Negeri 28 Merangin in the classroom VIIIshows that most of the learning outcomes of class VIII students have not reached the Minimum Completeness Criteria (MCC). The purpose of this study was to identify and describe the applicaation of the Guided Note Taking method with Mind Mapping media to improve integrated science learning outcomes.Classroom Action Research with a sample of 22 students consisting of 12 male students and 10 female students.This researcher uses two cycles and haas four staages, namely: 1) Planning, 2) Implementation, 3) Observation, the last stage is 4) Reflection. The results showed that the percentage of learning activities in the first cycle of student learning activities was 77% while student activities from cycle I to cycle II obtaained an increase of 13%. So student learning activities are said to be good because they have reached the success criteria of 90%. Integrated science learning outcomes with the subject of the human excretory system, the average score of students in the first cycle is 69.86 with a completeness percentage of 55% then followed by the second cycle the student average score reaches 80.72 with a classical percentage of 87%. Cycle II student learning outcomes have reached the Minimum Completeness Criteriaa(MCC) that has been set is 70.00 with a percentage of completeness 87% of students succeedIt was concluded that student learning outcomes increased.